Enhanced atrazine degradation is widespread across the United States. Issue 9 (19th April 2017) - Mueller, Thomas C; Parker, Ethan T; Steckel, Larry; Clay, Sharon A; Owen, Micheal DK; Curran, William S; Currie, Randall; Scott, Robert; Sprague, Christy; Stephenson, Daniel O; Miller, Donnie K; Prostko, Eric P; et al.
Abstract: BACKGROUND: Atrazine (ATZ) has been a key herbicide for annual weed control in corn, with both a soil and post‐emergence vegetation application period. Although enhanced ATZ degradation in soil with a history of ATZ use has been reported, the extent and rate of degradation in the US Corn Belt is uncertain. We show that enhanced ATZ degradation exists across much of the country. RESULTS: Soils from 15 of 16 surveyed states had enhanced ATZ degradation. The average ATZ half‐life was only 2.3 days in ATZ history soils, compared with an average 14.5 days in soils with no previous ATZ use, meaning that ATZ degrades an average 6 times faster in soils with previous ATZ use. CONCLUSION: When ATZ is used for several years, enhanced degradation will undoubtedly change the way ATZ is used in agronomic crops and also its ultimate environmental fate. © 2017 Society of Chemical Industry